Rencana penataan promenade di Pantai Padang Galak, Desa Kesiman Petilan, Kecamatan Denpasar Timur, Kota Denpasar - Prabawa, I Gusti Agung Ngurah; Yusiana, Lury Sevita; Mayun, Ida Ayu (Jurnal Arsitektur Lansekap; Vol.6, No.1, April 2020, 2020)
Padang Galak Beach is one of beach in Denpasar City that has a promenade as an access to human circulation. This promenade is well-located on Padang Galak Beach, but it is less organized and its potential has not been maximized. This study aims to identify and analyze the potential and constraints of physical aspects, vegetation, and activities on the Padang Galak Beach Promenade and conceptualize planning on the site. The study used survey methods with data collection techniques through observation, interviews, literature studies and questionnaires. The stages of this study were based on landscape planning which includes inventory, analysis, synthesis and conceptualization. The results showed that the basic concept used in this planning was intended to accommodate visitors in carrying out recreational and sports activities. The basic concept then become development concept that includes the concepts of space, the concept of circulation and the concept of green. The concept of space includes active and passive space, the concept of circulation includes two distribution between cyclist and promenade s, the concept of green includes the use of vegetation with types of groundcover and shade trees. This arrangement plan was expected to organize and develop the Padang Galak Beach area.